CHANGES IN THE TERRITORIAL STRUCTURE OF THE US AUTOMOTIVE INDUSTRY (Scientific journal of the Fergana State University, 2024)
The article presents a brief history of the formation of the automobile industry in the United States of America, changes in automobile production over the years, conditions and factors influencing the development of its territorial structure, as well as geographical changes in the industry and its importance for the country's economy. Additionally, information is provided on the major automobile manufacturing states in the United States in subsequent years, the number of suppliers associated with them, and information on the largest automobile manufacturing companies in the United States.